Muscle strength measurements reflecting the extent of complete subscapularis tears: reliability in patients with rotator cuff tears - Wataru Sahara, MD, PhD; Keishi Takagi, PT; Shuhei Tada, PT; Daichi Yamada, PT; Hiroki Kiya, PT; Hiroto Hanai, MD, PhD; Shoji Konda, PhD; Seiji Okada, MD, PhD (JSES International)
Background: While several clinical tests for diagnosing subscapularis (SSC) tears have been reported, no quantitative method reflecting tear size has been established. This study investigated muscle strength measurements that best reflect the extent of SSC tears and clarified their reliability. Methods: We analyzed 107 patients (111 shoulders) who underwent arthroscopic surgery for rotator cuff tears, assessing preoperative and postoperative muscle strength. Isometric internal rotation strength was measured by using a handheld dynamometer using three techniques: the belly-press, Napoleon, and bear-hug techniques. The correlation between the extent of complete SSC tears and preoperative strength for each technique was assessed using Spearman’s rank correlation coefficient. Intrarater reliability was assessed using the intraclass correlation coefficient (ICC) (1, 3), minimal detectable change (MDC), and MDC% based on three preoperative measurements on the operated side. Test-retest reliability was evaluated using these parameters from measurements on the nonoperated side preoperatively and at 6- and 12-month postoperative intervals. Results: The correlation coefficient between the extent of SSC tears and the strength of each muscle was approximately −0.45 for all techniques, indicating a weak negative correlation. The intrarater reliability for all techniques showed ICC (1, 3) >0.95, MDC <10 N, and MDC% of approximately 10%. The Napoleon technique demonstrated the highest test-retest reliability, with ICC (3, 1) of 0.87, MDC of 17 N, and MDC% of 21%. Conclusion: The Napoleon technique provided more stable muscle exertion than the other methods. The results may aid in determining whether postoperative muscle strength recovery falls within the range of measurement error.